Supporting "the best and brightest" in science and engineering NSF Graduate Research Fellowships - Freeman, Richard B. 1943-; Chang, Tanwin; Chiang, Hanley (National Bureau of Economic Research, 2005)
"The National Science Foundation's (NSF) Graduate Research Fellowship (GRF) is a highly prestigious award for science and engineering (S&E) graduate students. This paper uses data from 1952 to 2004 on the population of over 200,000 applicants to the GRF to examine the determinants of the number and characteristics of applicants and the characteristics of awardees. In the early years of the program, GRF awards went largely to physical science and mathematics students and disproportionately to white men, but as the composition of S&E students has changed, larger shares have gone to biological sciences, social sciences, and engineering, and to women and minorities. The absolute number of awards has varied over time, with no trend. Because the number of new S&E college graduates has risen, the result is a sharp decline in the number of awards per S&E bachelor's graduate
Keywords: National Science Foundation (U.S.) -- Funds and scholarships; Engineering students -- Scholarships, fellowships, etc; Science students -- Scholarships, fellowships, etc